WOMEN DRIVERS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Women do more work than men in the field and on the farm, yet mechanisation tends to favour men. A recent study was undertaken by FARMESA (Farm-Level Applied Research Methods in East and Southern Africa) and FAO-AGSE on the potential for improving...